"Age is just a number"; frailty as a marker of peri‐operative risk in head and neck surgery: Systematic review and meta‐analysis. Issue 8 (2nd June 2022) - Cleere, Eoin F.; Davey, Matthew G.; O'Neill, James P.
Abstract: Background: Frailty refers to a patient's reduced capacity to withstand stressors due to a reduction in physiologic reserves. We assessed the impact of frailty on outcomes following head and neck surgery. Methods: We performed a systematic review in accordance with the PRISMA guidelines. Meta‐analysis was performed using the Mantel–Haenszel method. Results: Fourteen studies incorporating 182 059 patients were included in qualitative synthesis with 15 953 (8.8%) of patients deemed as frail. Meta‐analysis incorporating nine studies demonstrated that frailty is associated with an increased 30 day postoperative morbidity (OR 2.74; 95% CI 1.98–3.80; p  < 0.01) and meta‐analysis with six studies suggested increased 30‐day mortality (OR 2.94; 95% CI 2.62–3.31; p  < 0.01). Preliminary meta‐analyses between two and five studies suggested that frail patients had reduced overall survival and were more likely to be discharged to a nonhome location or readmitted within 30 days. Conclusions: Frailty appears to be associated with poor short‐term outcomes following head and neck surgery and may improve understanding of an individual patient's peri‐operative risk.